2021
DOI: 10.1158/2159-8290.cd-20-1378
|View full text |Cite
|
Sign up to set email alerts
|

AXL Inhibition in Macrophages Stimulates Host-versus-Leukemia Immunity and Eradicates Naïve and Treatment-Resistant Leukemia

Abstract: Acute leukemias are systemic malignancies associated with a dire outcome. Due to low immunogenicity, leukemias display a remarkable ability to evade immune control and are often resistant to checkpoint blockade. Here, we discover that leukemia cells actively establish a suppressive environment to prevent immune attacks by co-opting a signaling axis that skews macrophages towards a tumor promoting tissue repair phenotype, namely the GAS6/AXL axis. Using aggressive leukemia models, we demonstrate that ablation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…Axl is also expressed by bone marrow-derived cells, dendritic cells, monocytes, natural killer cells, and platelets [36][37][38][39][40][41][42]. A study by Tirado-Gonzalez and colleagues also demonstrated that Axl-expressing leukemia-associated macrophages contribute to immune suppression and impair the functions of NK-and T-cell-mediated tumor cell killing [43].…”
Section: Gas6/axl Pathway In Cancermentioning
confidence: 99%
“…Axl is also expressed by bone marrow-derived cells, dendritic cells, monocytes, natural killer cells, and platelets [36][37][38][39][40][41][42]. A study by Tirado-Gonzalez and colleagues also demonstrated that Axl-expressing leukemia-associated macrophages contribute to immune suppression and impair the functions of NK-and T-cell-mediated tumor cell killing [43].…”
Section: Gas6/axl Pathway In Cancermentioning
confidence: 99%
“…However, these promising results need to be validated in the ongoing randomized placebo-controlled phase III trial (NCT04313881). Besides targeting CD47, ablation of the AXL receptor in macrophages has been shown to enable NK cell- and T-cell-mediated antitumor immune responses and to restore sensitivity to PD1 inhibition in preclinical leukemia models ( Tirado-Gonzalez et al 2021 ).…”
Section: Immune Therapies In Amlmentioning
confidence: 99%
“…High levels of MERTK and/or AXL have also been implicated in drug resistance and radioresistance [ 54 , 55 , 60 , 69 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ]. Increased MERTK or AXL expression in NSCLC correlated with chemotherapy resistance [ 51 , 66 , 70 , 87 , 88 , 89 ].…”
Section: Oncogenic Roles For Mertk and Axlmentioning
confidence: 99%
“…LPS challenge led to over-produced TNFα in Mertk kd mice, which lack the tyrosine kinase signaling domain, due to hyper-activation of NFκB [ 45 , 153 ]. Inhibition of MERTK by knockout of Mertk in mice, neutralization of TAM kinase signaling using a recombinant MERTK-Fc protein as a ligand sink or a GAS6 blocking antibody, and knockout of AXL in macrophages also impaired M2-macrophage anti-inflammatory phenotypes, decreased immunosuppressive IL-10 production, and increased pro-inflammatory IL-12 release [ 86 , 143 , 154 , 155 ]. These cytokine alterations lead to expansion of anti-tumor CD8 + T lymphocytes and inhibition of tumor growth and metastasis ( Figure 3 B).…”
Section: Oncogenic Roles For Mertk and Axlmentioning
confidence: 99%
See 1 more Smart Citation